2015
DOI: 10.1186/s12888-015-0567-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between suicidal behaviour and impaired glucose metabolism in depressive disorders

Abstract: BackgroundDisturbances in lipid metabolism have been linked to suicidal behaviour, but little is known about the association between suicide risk and abnormal glucose metabolism in depression. Hyperglycaemia and hyperinsulinaemia may increase the risk of depression and also the risk for suicide, we therefore studied associations between suicidal behaviour and disturbances in glucose metabolism in depressive patients who had been referred to depression nurse case managers.MethodsPatients aged 35 years and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 39 publications
2
61
0
2
Order By: Relevance
“…The severity of depressive symptoms (DS) was captured using the 21-item Beck Depression Inventory (BDI-21) (Beck et al, 1961), which was completed by the participants. The cut-off point was set to ≥10 (Koponen et al, 2015). The psychiatric diagnosis and number of other psychiatric comorbidities were confirmed and obtained with a diagnostic Mini-International Neuropsychiatric Interview (M.I.N.I.)…”
Section: Data Sourcesmentioning
confidence: 99%
“…The severity of depressive symptoms (DS) was captured using the 21-item Beck Depression Inventory (BDI-21) (Beck et al, 1961), which was completed by the participants. The cut-off point was set to ≥10 (Koponen et al, 2015). The psychiatric diagnosis and number of other psychiatric comorbidities were confirmed and obtained with a diagnostic Mini-International Neuropsychiatric Interview (M.I.N.I.)…”
Section: Data Sourcesmentioning
confidence: 99%
“…Koponen revealed in his research that higher level of blood glucose for the OGTT at baseline and 2 hours were found in depression patients with suicide attempt compared to those without suicide attempt [23]. Other studies also showed the relationship between high level of blood glucose and suicide [20,29].…”
Section: Discussionmentioning
confidence: 97%
“…For example, Ji Hyun Baek et al suggested that in MDD patients , the serum lipids levels are associated with suicide attempts [22]. Hannu Koponen et al indicated that glucose disturbances and lipid metabolism commonly exist in the groups of patients with depression aged 35 years and older [23],their results could be better if the subjects of depression are further subdivided according to the degrees. Since of all the age groups, the incidence of suicide in youth is higher.…”
mentioning
confidence: 99%
“…For example, Forsman et al () studied 17 SV and 27 nonsuicide controls and compared glucose lactate levels and HbA1c; they found that mean HbA1c was higher and mean estimated blood glucose was lower among SV. In addition, there is a hypothesis that hyperglycemia and hyperinsulinemia may increase the risk for depression and suicide; the group of Koponen, Kautiainen, Leppanen, Mantyselka, and Vanhala () studied the associations between SB and disturbances in glucose metabolism in depressive subjects. These researchers in sample of 448 depressive patients concluded that insulin resistance and disturbance in glucose and lipid metabolism are more common in depressive patients with SB.…”
Section: Discussionmentioning
confidence: 99%